Plasmonic Electrically Functionalized TiO2 for High‐Performance Organic Solar Cells. (27th March 2013) - Zhang, Di; Choy, Wallace C. H.; Xie, Fengxian; Sha, Wei E. I.; Li, Xinchen; Ding, Baofu; Zhang, Kai; Huang, Fei; Cao, Yong
Abstract Optical effects of the plasmonic structures and the materials effects of the metal nanomaterials have recently been individually studied for enhancing performance of organic solar cells (OSCs). Here, the effects of plasmonically induced carrier generation and enhanced carrier extraction of the carrier transport layer (i.e., plasmonic‐electrical effects) in OSCs are investigated. Enhanced charge extraction in TiO2 as a highly efficient electron transport layer by the incorporation of metal nanoparticles (NPs) is proposed and demonstrated. Efficient device performance is demonstrated by using Au NPs incorporated TiO2 at a plasmonic wavelength (560–600 nm), which is far longer than the originally necessary UV light. By optimizing the concentration ratio of the Au NPs in the NP‐TiO2 composite, the performances of OSCs with various polymer active layers are enhanced and efficiency of 8.74% is reached. An integrated optical and electrical model, which takes into account plasmonic‐induced hot carrier tunneling probability and extraction barrier between TiO2 and the active layer, is introduced. The enhanced charge extraction under plasmonic illumination is attributed to the strong charge injection of plasmonically excited electrons from NPs into TiO2. The mechanism favors trap filling in TiO2, which can lower the effective energy barrier and facilitate carrier transport in OSCs.